2019
DOI: 10.32098/mltj.01.2014.03
|View full text |Cite
|
Sign up to set email alerts
|

PRP treatment effects on degenerative tendinopathy - an in vitro model study

Abstract: Platelet-rich plasma (PRP) has become a popular option for the treatment of injured tendons. However, the efficacy of PRP treatment is a matter of heated debate in orthopaedics and sports medicine. In this study, we used a cell culture model to evaluate the potential effects of PRP treatment on degenerative tendinopathy. The in vitro model, which uses the current concept of "diseases-in-adish", consisted of tendon stem/progenitor cells (TSCs) that were derived from rabbit tendons and cultured in differentiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…38 Fourth, PRP in the KGN-PRP pair serves as a scaffold that functions as a "retainer" of KGN solution, thus preventing its diffusion into the surrounding tissues. The use of KGN alone without PRP will result in diffusion or ‘leakage’ that may lead to the formation of cartilage-like tissue in otherwise healthy tendon as shown in our previous study 45 and, as a result, may compromise tendon structure and function. Furthermore, PRP also has numerous growth factors that stimulate the healing of soft tissues 20,46 such as tendons, 47 and attracts other stem cells such as BMSCs that may further enhance tissue healing.…”
Section: Discussionmentioning
confidence: 75%
“…38 Fourth, PRP in the KGN-PRP pair serves as a scaffold that functions as a "retainer" of KGN solution, thus preventing its diffusion into the surrounding tissues. The use of KGN alone without PRP will result in diffusion or ‘leakage’ that may lead to the formation of cartilage-like tissue in otherwise healthy tendon as shown in our previous study 45 and, as a result, may compromise tendon structure and function. Furthermore, PRP also has numerous growth factors that stimulate the healing of soft tissues 20,46 such as tendons, 47 and attracts other stem cells such as BMSCs that may further enhance tissue healing.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, there is no clear conclusion regarding the curative effect of PRP in T+. By recently assessing PRP in a rat model [with fixed platelet concentration in PRP (x3) and no adjuvant], with a systematic clinical and US follow-up and histological examination, we have previously provide strong evidence that PRP might be a useful strategy to treat T+ 15 . In this study, we used the same setup, animal model, and controlled PRP preparation protocol as described in our pre-clinical model.…”
Section: Discussionmentioning
confidence: 99%
“…PRP can be directly injected into tendons to enhance local platelet concentration. Numerous in vitro [11][12][13] and animal studies using this technique have been performed in animal models of tendon rupture or T+ with results demonstrating improvement of clinical and histological repair 14,15 . Similarly, human studies have shown discordant results regarding pain reduction in different tendon locations 16 .…”
Section: Protocol 1 (Prp Systemic Effect)mentioning
confidence: 99%
“…Limitations of the present study were small sample number, short experimental period, lack of biomechanical evaluation and that the present animal model reproduced the early-stage tendinopathy, not in the late-stage, which was characterized by fibrosis, lipid depositions, proteoglycan accumulation and calcification in the tendon. Zhang showed that an autologous platelet-rich clot releasate could not reverse the nontenogenic differentiation of tendon stem/progenitor cells which were pre-treatment in non-tenogenic media for 2 days in vitro model and the study suggested that the injection of PRP in clinics may not be able to effectively reverse the degenerative conditions of late-stage tendinopathy 39 . It was still uncertain whether the PRP therapy was effective for the latestage tendinopathy or not.…”
Section: Groupmentioning
confidence: 99%